Revascularization Failure: Percutaneous Coronary Intervention or Coronary Artery Bypass Grafting - Islam, AHM Waliul; Reza, AQM; Munwar, Shams; Talukder, Shahabuddin (Cardiovascular Journal, 2022)
Coronary artery disease (CAD) is one of the leading causes of mortality and morbidity in our Bangladeshi patient population. Percutaneous coronary intervention (PCI) or Coronary artery bypass grafting (CABG) are the gold standard of revascularization to treat these group of patients. Both treatment modalities may contribute to both short term and long-term excellent benefit with the relief of symptoms and improves quality of life. Beside the availability of modern techniques along with 3rd generation Drug eluting stents (DES) for PCI and uses of arterial conduit in bypass surgery, in long-term follow-up, many of the patient needs repeat revascularization. In Bangladesh, many of the centers are doing state of the art treatment with the available of most of interventional aids in treating complex PCI as well as primary PCI. Similarly, CABG with the advent and available expertise, minimal invasive bypass surgery or beating heart surgery, facilitate CABG more convenient for patient and surgeons as well. Exact data on stent occlusion or graft failure that may leads to repeat revascularization is not well understood in our circumstances. We need to form a common consensus, if needed, to form a national registry or database to follow up PCI or CABG patients who develop subsequent revascularization failure and address the reason behind. Thus, to reduce the needs of repeat revascularization and improve long term quality of life. Cardiovasc j 2022; 15(1): 81-85